1975
DOI: 10.1104/pp.55.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nonautotrophic Carbon Dioxide Fixation to Protein Synthesis in Suspension Cultures of Paul's Scarlet Rose

Abstract: Bicarbonate-'4C was provided to 5-and 11-day-old suspension cultures of Paul's Scarlet rose, and the incorporation of 4C into lipid, protein, amino acids, and organic acids was determined. The rate of bicarbonate uptake was approximately the same by 5-and 11-day-old cells, but the distribution of 4C among cell constituents was markedlv different. In 5-dav-old cells a larger proportion of the "4C entered protein, whereas in 11-day-old cells there was a greater tendency for "4C to accumulate in malate.The '4C in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…However, it has been reported that the activity of PEPC is high in exponentially growing cell cultures (4, 5, 18,19) as well as in callus cultures (21). Similar observations (10, 13) suggesting that the carbon fixed by an increased activity of PEPC might be important for a supply of carbon skeletons to biosynthetic pathways in young, exponentially growing parts of intact plants have also been made.…”
supporting
confidence: 57%
“…However, it has been reported that the activity of PEPC is high in exponentially growing cell cultures (4, 5, 18,19) as well as in callus cultures (21). Similar observations (10, 13) suggesting that the carbon fixed by an increased activity of PEPC might be important for a supply of carbon skeletons to biosynthetic pathways in young, exponentially growing parts of intact plants have also been made.…”
supporting
confidence: 57%
“…The label from bicarbonate went mainly into organic acids and amino acids and a small amount into lipids ( Figure 6). Similar results have been observed in sycamore [17] and Paul's Scarlet rose [9] cells. The incorporation of label from bicarbonate into organic and amino acids was greater in the pith-phloem explants than in the subcultured callus from day 2 onwards.…”
Section: Resultssupporting
confidence: 77%
“…Since this cell line has the tendency to grow as aggregates (Nesius & Fletcher 1975) the volume of individual cells was difficult to determine. To ensure an accurate measurement, two methods were used to determine cell volume: the classical, micrometer method (Nesius et al 1972) was applied to external cells and a new method was developed using volume of the cell mass divided by the number of cells in the aggregate as determined by nuclear DNA fluorochromes.…”
Section: Cell Volume Determinationsmentioning
confidence: 99%
“…Each period lasts several days and is similar to one of the developmental stages characteristic of cells present in meristematic regions of intact plants. With rose cultures it has been shown that as the cells progress through the various growth periods, a number of important physiological processes, organic acid metabolism (Fletcher & Beevers 1970), amino acid synthesis (Hunt & Fletcher 1976;Nesius & Fletcher 1975), respiration (Hunt & Fletcher 1976), and protein synthesis (Hunt & Fletcher 1976;Mohanty & Fletcher 1980) change dramatically. It has also been established with various cell lines that during culture growth cells experience numerous ultrastructural changes (Fowke 1986;Sutton-Jones & Street 1968).…”
Section: Introductionmentioning
confidence: 99%